The Influence of Social Media Instagram @Coummuterline on Sales of Multi Trip Cards (KMT) at PT. Indonesian Commuterline Train - Evitha, Yuli; Hidayat, Cindy Maulindra (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Instagram social media can be used by all levels of society to carry out daily activities, one of which is marketing activities, one of which is marketing activities. By using Instagram as a promotional strategy you can increase sales and interest in products without spending a lot of money and effort. Apart from that, promoting products on Instagram can make it easier for consumers to buy and find information about the products offered. This research method uses a quantitative method a questionnaire via Google from. The population in this study was 322,000 Instagram followers @commuterline. The number of samples for this research was the total Instagram population using the Slovin formula, so that a sample of 100 respondents was obtained. The results of the research show that the determinant coefficient test (R2) value of R square is 0.604. This value shows that the effectiveness of Instagram media is influenced by 60.4% of sales variables. So it can be concluded that Instagram social media has an influence on sales effectiveness of 60.4% and the remaining 39.6% is influenced by other factors.